[im]Possible Experiences: a look at experience, art and education (Revista Apotheke, 2025)
The article investigates experience as an essential element in the construction of human knowledge, highlighting its relevance to art and education. Based on authors such as John Dewey (1979), Jorge Larrosa (2002; 2015), and Italo Calvino (1994), the text discusses how experience goes beyond technical and academic knowledge, offering a subjective and transformative perspective on reality. The research explores the proposal “Experiência [Im]possível” (“[Im]possible Experience”), developed in an educational context, reflecting on the importance of pause, feeling, and perception in contemporary society. It argues that experience and art are forms of resistance against neoliberal productivism, enabling a more sensitive and democratic approach to education. The study concludes that valuing experiential knowledge is a political act that restores humanity in an accelerated and mechanized world.
Keywords: Experience; Art; Education